2014
DOI: 10.1371/journal.pone.0112273
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variations of Crop Fertilization and Soil Fertility in the Loess Plateau in China from the 1970s to the 2000s

Abstract: Increased fertilizer input in agricultural systems during the last few decades has resulted in large yield increases, but also in environmental problems. We used data from published papers and a soil testing and fertilization project in Shaanxi province during the years 2005 to 2009 to analyze chemical fertilizer inputs and yields of wheat (Triticum aestivum L.) and maize (Zea mays L.) on the farmers' level, and soil fertility change from the 1970s to the 2000s in the Loess Plateau in China. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 58 publications
2
15
0
1
Order By: Relevance
“…In the present study, pH, EC, primary and secondary macro and micronutrients vary significantly across seasons, localities and stage of the crop. Similar observations have been reported from studies elsewhere (Troelstra et al 1990;Wang et al 2014). This can be due to differences in the uptake of nutrients by the crops during growing and harvesting periods, rate of fertilizer inputs and other natural seasonal variations (Gornall et al 2010;Turner et al 2013).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the present study, pH, EC, primary and secondary macro and micronutrients vary significantly across seasons, localities and stage of the crop. Similar observations have been reported from studies elsewhere (Troelstra et al 1990;Wang et al 2014). This can be due to differences in the uptake of nutrients by the crops during growing and harvesting periods, rate of fertilizer inputs and other natural seasonal variations (Gornall et al 2010;Turner et al 2013).…”
Section: Discussionsupporting
confidence: 85%
“…In the case of Rajouri district, even after significant increase in addition of N and P, rice in the yields of rice, maize and wheat are insignificant. Incidentally, it is to be noted that higher addition of N and P could also lead to deficiency of K and micronutrients (Singh 2008;Wang et al 2014). The prescribed usage of N fertilizer in the crop vary but on an average it is 50 kg/ ha (Digest of Statistics 2012) lower than in plains (80 kg/ha, Parihar 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Gong et al, (2013) also indicated that the contribution of soil productivity was significantly correlated with soil organic carbon, total nitrogen, available nitrogen, available phosphorus and available potassium in wheat with long-term soil fertility experiments [32]. The same results were reviewed from the 1970s to the 2000s in the Loess Plateau in China by Wang et al (2014) [33]. Results showed that changed trends of soil organic matter content under different treatments in two years were similar.…”
Section: Discussionmentioning
confidence: 99%
“…In 1950, when no mineral fertilizers were used (Zhu and Chen, 2002), nutrient losses by erosion likely exceeded nutrient supply. The reduction of relative nutrient losses is mainly due to the increase of nutrient inputs: the reduction of nutrient losses associated with a reduction of erosion rates is relatively less important (Wang et al, 2014a). The average TER on arable land is now close to what was long considered to be an acceptable soil loss tolerance level Renard et al, 1997).…”
Section: Nutrient Losses and Agricultural Productivity Reduction By Smentioning
confidence: 98%
“…Comparison of fertilizer inputs (N and P) and losses due to topsoil erosion (Tg) on arable land on the CLP in 1980 and 2000. Nutrients inputs were estimated by multiplying fertilizer input per unit area (kg ha −1 ) (Wang et al, 2014a) with the total cropland area (ha). Nutrient losses due to erosion were estimated by multiplying the amount of sediment mobilized by topsoil erosion and the nutrient content of topsoil under different land uses (Liu et al, 2013 (2000) amounts and relative losses of nutrients by erosion exceeded 50 % of the input at that time (Table 4).…”
Section: Nutrient Losses and Agricultural Productivity Reduction By Smentioning
confidence: 99%